ANALISIS BEBAN KOGNITIF SISWA DALAM PROSES PEMBELAJARAN KELAS VII SMP DITINJAU DARI COGNITIVE LOAD THEORY - Dwi Evayanti Hamrullah; Farida Febrianti (STKIP Subang, 2026)
This study aims to analyze the cognitive load of seventh-grade junior high school students in the learning process from the perspective of Cognitive Load Theory. The study employed a qualitative descriptive approach using the case study method. Data were collected through classroom observations and the distribution of a Google Forms-based questionnaire to seventh-grade students. The results indicate that students experienced difficulty understanding the material when the teacher delivered it too quickly and when classroom conditions were not conducive to learning, thereby disrupting their concentration. In addition, some students required further explanation to understand the material presented. Based on Cognitive Load Theory, these conditions indicate the presence of extraneous cognitive load, which overburdens students’ working memory capacity. Therefore, teachers need to implement more structured learning strategies, deliver material in stages, and manage the classroom more effectively to reduce students’ cognitive load. Penelitian ini bertujuan untuk menganalisis beban kognitif siswa dalam proses pembelajaran kelas VII SMP ditinjau dari Cognitive Load Theory. Penelitian menggunakan pendekatan deskriptif kualitatif dengan metode studi kasus. Data diperoleh melalui observasi kelas dan penyebaran angket berbasis Google Form kepada siswa kelas VII. Hasil penelitian menunjukkan bahwa siswa mengalami kesulitan memahami materi ketika guru menyampaikan materi terlalu cepat dan kondisi kelas kurang kondusif sehingga mengganggu konsentrasi belajar siswa. Selain itu, beberapa siswa membutuhkan penjelasan ulang untuk memahami materi yang diberikan. Berdasarkan Cognitive Load Theory, kondisi tersebut menunjukkan adanya extraneous cognitive load yang menyebabkan kapasitas working memory siswa menjadi terbebani. Maka, guru perlu menerapkan strategi pembelajaran yang lebih terstruktur, penyampaian materi secara bertahap, dan pengelolaan kelas yang lebih efektif untuk mengurangi beban kognitif siswa.